Highly efficient multi-site synergistic catalysis of a polyoxovanadate-based metal–organic framework for benzylic C–H bond oxidation. Issue 31 (19th July 2022) - Dang, Tian-Yi; Li, Run-Han; Tian, Hong-Rui; Guan, Wei; Lu, Ying; Liu, Shu-Xia
Abstract : Multi-active site synergy in a polyoxovanadate-based mixed-valence copper metal–organic framework for efficient catalysis of C–H bond oxidation of benzylic compounds. Abstract : The selective oxidation of C–H bonds of benzylic compounds to synthesize high-value-added ketones remains a challenge under mild conditions, and the ambiguity of its oxidation mechanism limits the further development of this field. In this work, we construct a polyoxometalate-based metal–organic framework (POMOF), [CuI2Cu II (bix)2 ]V4 O12 (1, bix = 1, 4-bis(imidazole-1-ylmethyl)benzene), successfully achieving the efficient oxidation catalysis of various benzylic compounds with outstanding conversion, selectivity and durability under mild conditions. Our experimental studies suggest that the highly catalytic activity of 1 derives from its attractive structure with multiple active sites, which consists of V V centers in a unique U-type V4 O12 4− (V4 ) cluster and Cu I and Cu II centers bridged to the V4 cluster. Importantly, further theoretical calculations indicate that there exists synergistic catalysis between Cu I /V4 sites and Cu II /V4 sites for 1 as catalyst in the oxidation of benzylic compounds, where the V4 cluster mainly provides deprotonation and oxidation sites, and the Cu I site plays a role in the reduction of the oxidant, while the Cu II site plays a role in the adsorption of the oxidant. This is the first POMOF whose catalytic mechanism towards the oxidation of benzylic C–H bonds is deeply studied through the combination of experiments and theoretical calculations, providing a new perspective for the design of related catalysts.